2023
DOI: 10.1016/j.jvoice.2021.02.025
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine on Voice: A Systematic Review

Abstract: Background. Caffeine is considered a dehydrating agent due to its diuretic effects and influences the body's fluid balance. The relationship between voice and hydration has been widely investigated and it is accepted that inadequate hydration has detrimental effects on phonation. Since dehydration negatively affects the vocal folds and caffeine is considered a dehydrating agent, it can be hypothesized that voice might be negatively affected by caffeine intake. This systematic review aims to summarize and appra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…This result reflects those of Azari et al's systematic review, which also found that caffeine consumption was the most frequently reported factor among teaching faculty [11]. This is anticipated, as caffeine consumption can induce dehydration and thus have a detrimental effect on phonation [28].…”
Section: Discussionsupporting
confidence: 86%
“…This result reflects those of Azari et al's systematic review, which also found that caffeine consumption was the most frequently reported factor among teaching faculty [11]. This is anticipated, as caffeine consumption can induce dehydration and thus have a detrimental effect on phonation [28].…”
Section: Discussionsupporting
confidence: 86%